Detective Jo Fournier : The Dancing Girls - Book 1 - Chouinard, Michelle M. (Michelle Marie) (London : Bookouture, an imprint of StoryFire Ltd., 2019)
"When Jeanine Hammond is found dead in a hotel in the picture-perfect town of Oakhurst, newly-promoted Detective Jo Fournier is thrown into a disturbing case. Who would murder this shy, loving wife and leave her body posed like a ballerina? Jo wants to know why Jeanines husband is so controlling about money, and where Jeanines wedding ring is, but before she and her team can get close to the truth, another woman is found strangled in a hotel, arms placed gracefully above her head like a dancer"--Back cover.
Keywords: Women detectives -- Fiction; Murder -- Investigation; Fiction; Serial murder investigation -- Fiction; Thrillers (Fiction); Detective and mystery fiction